Ethnomathematics Role As an Encouragement of the Growth of Student’s Nationalism - ., Zaenuri; Dwidayati, Nurkaromah; Suyitno, Amin (KnE Social Sciences, 2019)
ThisarticlehasbeenprecededbyaresearchactivityinGuangxiChinaandcollaborated with Prof. Guo Yuanbing, Ph.D, Deputy Director of Guangxi Normal University. The research method used a qualitative approach. The research activities included ﬁeld observationstoexploreformsofethnomathematics.Theproblem:Howwastheroleof ethnomathematics as an encouragement of the growth of students’ nationalism? The objectives were: (1) Finding the role of ethnomathematics in encouraging the growth of students’ nationalism. (2) Finding the objects of ethnomathematics that can encourage the growth of students’ nationalism. Data analysis includes: data reduction, data display, data interpretation, and conclusion/veriﬁcation. The results were as follows: (1) Thelearningbyapplyingofethnomathematicsapproachcanplayaroleinencouraging thegrowthofstudents’nationalism.(2)Tooptimizetheroleofethnomathematicsasan encouragement of the growth of the spirit of nationalism, the teacher needs to choose the objects of ethnomathematics based on the work of the nation’s own. Keywords: Ethnomathematics, Mathematics Learning, Nationalism